Topological spatial relations for circular spatially extended points: an overview - Santos, Maribel Yasmina (2010)
Spatial relations between geographical objects include topological spatial relations, that are relations that are preserved under continuous transformations of the space, such as rotation or scaling. Research on topological spatial relations between different types of objects (points, lines, or regions) has been undertaken for many years. In this chapter, it is presented the particular case of the topological spatial relations that can exist between a Circular Spatially Extended Point and a region, a Circular Spatially Extended Point and a line, and two Circular Spatially Extended Points. For the several topological spatial relations, the geometrical representation of the relations is also presented.